Enhancing pre-service teachers’ understanding of pedagogical key ideas by integrating ChatGPT in ODL course tutorials - Chew, Cheng Meng; Tan, Saw Fen; Ping, Por Fei; Leong, Alexander Funk Yun (Human Resource Management Academic Research Society, 2025)
This study aimed to enhance pre-service teachers’ understanding of pedagogical key ideas by integrating ChatGPT in the open and distance learning (ODL) pedagogy course tutorials. Purposive sampling was employed in this case study to select nine pre-service teachers from an ODL university. Data were collected through the participants’ reflective reports, video recordings of their presentation of reflective reports, and revised reflective reports. Descriptive statistics and Friedman test with post hoc Wilcoxon signed rank tests were used to analyze the data. The findings showed that 55.56% of the participants achieved a substantial understanding of pedagogical key ideas in their initial reflective reports and their presentation of reflective reports, respectively, while 44.45% achieved a partial understanding. The participants improved in their revised reflective reports after incorporating feedback from the tutor and peers, with 55.56% achieved a high understanding of pedagogical key ideas, 33.33% achieved a substantial understanding, while 11.10% achieved a partial understanding. The Friedman test with post hoc Wilcoxon signed rank tests showed that there was a significant difference in the participants’ understanding of pedagogical key ideas before and after, and during and after the tutorials.